The Incidence of Radix Entomolaris in Mandibular First Permanent Molars in a Saudi Arabian Sub-Population - Laila A. Bahammam,; Hammam A. Bahammam, (Journal of King Abdulaziz University: Medical Sciences, 2023)
The aim of this study was to investigate the incidence of radix entomolaris in mandibular first permanent molars in Saudi Arabian subpopulation. A total of 280 extracted mandibular first permanent molar were included in the study. The teeth were examined visually and the number of roots was recorded. The results showed that the majority of cases had two roots 93.9% (263 teeth), whereas the remaining 6.07% (17 teeth) had three roots. It is apparent from the previously reported studies and the findings of this study, that a higher frequency of occurrence of radix entomolaris in mandibular first molars in Saudi Arabian population than in other populations in west Asia. In addition to a higher frequency of occurrence in the East Asian population than in the West.